Ecological response of phytoplankton to the oil spills in the oceans. Issue 1 (1st January 2019) - Tang, Danling; Sun, Jing; Zhou, Li; Wang, Sufen; Singh, Ramesh P.; Pan, Gang
Abstract: Oil spills in oceans have substantial influence on marine ecosystems. This study investigates 21 oil spills in the world. Analyzing Chlorophyll- a (Chl- a ) from Moderate Resolution Imaging Spectroradiomerer (MODIS) data after Penglai oil spills on 4 June 2011, found a bloom with peak value of Chl- a (13.66 mg m −3 ) spread over an area of 800 km 2 during 18–25 June 2011, and a pronounced increase in the monthly Chl- a concentration (6.40 mg m −3 ) on June 2012 in the Bohai Sea. Out of the 21 oil spills, 14 blooms were observed, while 11 blooms associated with oil spills in the time interval of 3–10 months. In total, about 75% blooms occurred during June–August. Among all 14 blooms, 72% appeared when temperature was warm (20–30 °C), 7% appeared when temperature was low (10–20 °C), and the remaining 21% occurred when temperature was lower than 10 °C. This research concludes that the odds of a phytoplankton bloom after an oil spillage are higher at the time of higher temperature (>20 °C). The short-term impact of the oil spills on ecosystem could mainly depend on the quantity and composition of oil, while the long-term impact of the oil spills on ecosystem could be related to biodegradation of microorganisms.